Pad material and retaining sealing material
By adopting a laminated cushion structure, the alternate configuration of the orientation layer and random layer of inorganic fibers and the distribution of adhesives, the existing cushion materials are solved during the winding process of the exhaust gas treatment body, and the cushion materials with high tensile strength and friction are achieved, ensuring the sealing performance of the exhaust gas purification device.
Patent Information
- Application Number
- CN202480003618.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing gaskets are prone to break due to tensile loads during winding of exhaust gas treatment bodies, and their tensile strength is insufficient, making it difficult to meet the needs of efficient sealing.
The pad material with a laminated pad structure is used to improve the tensile strength and friction force of the pad material through the alternating configuration of the orientation layer and the random layer of the inorganic fibers, combined with the distribution of the adhesive.
The tensile strength and friction of the cushion material are significantly improved, the risk of fracture during winding is reduced, the stable contact between the exhaust gas treatment body and the cushion material is ensured, and the sealing performance of the exhaust gas purification device is improved.
Smart Images

Figure CN119731422A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a gasket and a holding sealing material. Background Art
[0002] The exhaust gas discharged from internal combustion engines such as diesel engines contains particulate matter (hereinafter also referred to as PM), and in recent years, the PM has become a problem that it is harmful to the environment and human body. In addition, since the exhaust gas also contains harmful gas components such as CO, HC, and NOx, there is also concern that these harmful gas components will affect the environment and human body.
[0003] Therefore, as exhaust gas purification devices for capturing PM in exhaust gas or purifying harmful gas components, various exhaust gas purification devices consisting of an exhaust gas treatment body (which is composed of porous ceramics such as silicon carbide and cordierite), a metal shell for accommodating the exhaust gas treatment body, and a holding sealing material (mat) disposed between the exhaust gas treatment body and the metal shell have been proposed. The holding sealing material (mat) is provided for the main purpose of preventing the exhaust gas treatment body from contacting with the metal shell covering its periphery and being damaged due to vibration or impact generated by the driving of the car, etc., and preventing exhaust gas from leaking from between the exhaust gas treatment body and the metal shell.
[0004] As a mat material used in such applications, Patent Document 1 discloses a holding sealing material, which is a holding sealing material composed of a mat of a specified thickness including inorganic fibers whose surface is covered with an adhesive layer, and is characterized in that the adhesive layer contains an organic adhesive and an inorganic adhesive, and when the mat is divided into three equal parts in the thickness direction into a first surface portion, a central portion, and a second surface portion, the amount of organic adhesive added to the first surface portion is greater than the amount of organic adhesive added to the central portion, and greater than the amount of organic adhesive added to the second surface portion.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-63925 Summary of the invention
[0008] Problems to be solved by the invention
[0009] When winding the mat material around the exhaust gas treatment body, the winding operation is sometimes performed while applying a tensile load to the mat material. In such an operation, if the tensile strength of the mat material is low, the mat material may be broken by the tensile load, which may cause a problem.
[0010] The tensile strength of the mat described in Patent Document 1 is also insufficient, and it is desired to improve the tensile strength of the mat.
[0011] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a mat material having high tensile strength.
[0012] Means for solving problems
[0013] The mat material of the present invention comprises a layered mat, wherein the layered mat comprises at least one oriented layer composed of inorganic fibers and having a uniform orientation direction, and at least one random layer composed of inorganic fibers and having a random orientation direction,
[0014] The above-mentioned laminated mat contains a binder.
[0015] The laminated mat constituting the mat of the present invention comprises an oriented layer and a random layer. The presence of the oriented layer can provide a mat that is not easily elongated and has high tensile strength.
[0016] In addition, the binder can easily penetrate into the random layer. By including the binder in the mat, the friction force on the mat surface can be increased.
[0017] In the mat material of the present invention, it is preferred that the oriented layers and the random layers are alternately laminated in the thickness direction, and the random layers are disposed on both outermost layers of the laminated mat.
[0018] When the adhesive is impregnated into the laminated mat, the adhesive is arranged in the outermost layer of the laminated mat and permeates from the random layer in the thickness direction of the laminated mat. Since the adhesive easily permeates the random layer but not the oriented layer, the adhesive is blocked by the oriented layer in the thickness direction of the laminated mat.
[0019] As a result, the binder content in the outermost layer of the laminated mat, which is in contact with the binder liquid for binder impregnation, increases. If the binder content is high, the frictional force increases, so if the outermost layer with a high binder content is used as the surface in contact with the exhaust gas treatment body requiring friction during winding, the displacement of the exhaust gas treatment body and the mat material can be prevented, and it can be preferably used.
[0020] In the mat material of the present invention, it is preferred that the layered mat contains at least one of an organic binder and an inorganic binder.
[0021] In the mat material of the present invention, when the laminated mat is divided into three equal parts in the thickness direction into a first surface portion, a central portion, and a second surface portion, the random layer is preferably arranged on the outermost layer of the first surface portion.
[0022] The content of the binder in the first surface portion is larger than the content of the binder in the central portion, and larger than the content of the binder in the second surface portion.
[0023] In the above mat, since the first surface portion contains a large amount of binder, if the first surface portion is used as a portion in contact with the exhaust gas treatment body, displacement between the exhaust gas treatment body and the mat can be prevented, and the mat can be preferably used.
[0024] In addition, the mat material is used in the exhaust gas purification device, but since the exhaust gas purification device is used in a high temperature environment, the binder (especially the organic binder) may volatilize. Therefore, for the mat material assumed to be used in the exhaust gas purification device, it is required not to increase the binder content.
[0025] In the above mat material, the content of the binder is increased in the first surface portion rather than in the entire mat material, so that the requirements for the binder content of the entire mat material can be met.
[0026] In the mat of the present invention, the content of the binder preferably satisfies the following relationship.
[0027] 0.4≤(central part / first surface part)
[0028] 0.2≤(second surface portion / first surface portion)
[0029] (Second surface part / central part)≤0.5
[0030] In addition, it is preferred that the content of the binder further satisfies the following relationship.
[0031] 0<(second surface part / central part)
[0032] If the adhesive contents of the first surface portion, the central portion, and the second surface portion satisfy the above relationship, when the first surface portion is brought into contact with the exhaust gas treatment body and wound, the friction between the mat and the exhaust gas treatment body is increased, and when assembled into the outer casing, interface sliding is not easily caused between the mat and the exhaust gas treatment body.
[0033] In the mat of the present invention, it is preferred that the inorganic fibers in the orientation layer contain 70% or more of inorganic fibers having an inclination angle of 60 to 90 degrees with respect to the width direction of the mat.
[0034] In the mat of the present invention, it is preferred that the tensile strength at break measured by a tensile test is 200 kPa or more.
[0035] Furthermore, the elongation at break measured by a tensile test is preferably 3.5 mm or less.
[0036] When the tensile strength at break and the elongation at break measured by a tensile test are within the above ranges, the mat can be more reliably prevented from breaking when being wound around an exhaust gas treatment body or the like.
[0037] In addition, when the tensile strength at break is high and the elongation at break is small, the variation in workability during winding is reduced.
[0038] The holding sealing material of the present invention is composed of the mat material of the present invention, and is used for holding an exhaust gas treating body in an exhaust gas purifying device.
[0039] The mat material of the present invention is a mat material that is not easily stretched and has high tensile strength, and therefore is not easily broken when being wound around an exhaust gas treatment body, and is suitable for use as a holding sealing material. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a perspective view schematically showing an example of a mat material.
[0041] Figure 2 yes Figure 1 The AA line cross-section of the mat material is shown.
[0042] Figure 3 It is a perspective view schematically showing an example of an alignment layer.
[0043] Figure 4 This is an example of a microscope photograph including inorganic fibers.
[0044] Figure 5 It is a perspective view schematically showing an example of a random layer.
[0045] Figure 6 is a cross-sectional view schematically showing a needle punched mat including a rivet portion.
[0046] Figure 7 It is a cross-sectional view schematically showing an example of an exhaust gas purification device.
[0047] Figure 8 It is a perspective view schematically showing an example of an exhaust gas treating body constituting the exhaust gas purification device.
[0048] Fig. 9 This is a perspective view schematically showing an example of a method for manufacturing an exhaust gas purification device. DETAILED DESCRIPTION
[0049] Hereinafter, an example of the mat material and the holding sealing material of the present invention will be described in detail with reference to the drawings.
[0050] Figure 1 It is a perspective view schematically showing an example of a mat material.
[0051] Figure 2 yes Figure 1 The AA line cross-section of the mat material is shown.
[0052] Figure 1The mat material 10 shown is a laminated mat 20 including an oriented layer 30 and a random layer 40 .
[0053] The three layers of the random layer 40a, the oriented layer 30, and the random layer 40b are arranged along the thickness direction of the laminated mat 20 ( Figure 1 and Figure 2 The random layer 40a and the random layer 40b are layers of the same specification.
[0054] The laminated mat 20 is Figure 1 The length of the pad is long (in the direction indicated by the double arrow L).
[0055] The laminate mat 20 has two main surfaces, a first main surface 23 and a second main surface 24. The first main surface 23 is a surface of the random layer 40a, and the second main surface 24 is a surface of the random layer 40b.
[0056] The laminated mat 20 has four side surfaces, and the side surfaces along the length direction of the laminated mat 20 are the first long side surface 25 and the second long side surface 26. Figure 1 The sides facing in the direction indicated by the double arrow W in the figure are the first short side 27 and the second short side 28.
[0057] The plan view of the laminated mat 20 is generally rectangular, with a concave portion formed on the first short side 27 and a convex portion formed on the second short side 28. When the mat is wound around an exhaust gas purification device, an exhaust gas treatment body, or an exhaust pipe having a cylindrical outer circumference, the concave portion and the convex portion are in a shape that fits into each other.
[0058] It should be noted that, in the mat material of the present embodiment, the shape of the portion to be fitted is a concave portion and a convex portion, but the shape of the portion to be fitted may be a combination of L shapes.
[0059] Figure 3 It is a perspective view schematically showing an example of an alignment layer.
[0060] Figure 3 3 shows an orientation layer 30, and shows schematically the inorganic fibers 31 constituting the orientation layer 30 together with their orientation directions. The orientation layer 30 is a layer composed of inorganic fibers, and the orientation directions of the inorganic fibers are uniform.
[0061] In the orientation layer, the inorganic fibers are preferably oriented in the direction along the main surface of the mat material ( Figure 3 In addition, it is preferred that the inorganic fibers have the same orientation direction in the length direction (LW plane direction) of the mat material. Figure 3 L direction) or width direction ( Figure 3 W direction) for orientation.
[0062] Figure 3In the oriented layer shown, the inorganic fibers are oriented in a direction along the longitudinal direction of the mat.
[0063] The "inorganic fibers have a consistent orientation direction" in this specification means that in a microscope photograph containing inorganic fibers, the angle of the inorganic fibers is measured relative to one direction of the shooting area (usually the lateral direction of the shooting area), and the result shows that more than 50% of the fibers by number are within the range of 75 to 90 degrees.
[0064] Figure 4 This is an example of a microscope photograph including inorganic fibers.
[0065] exist Figure 4 The inorganic fibers 31 are reflected in the photograph shown. Figure 4 In the images, it can be visually confirmed that many inorganic fibers are oriented in the longitudinal direction (90° direction) of the photographed area. In addition, 52% of the inorganic fibers have an angle θ of 75 to 90 degrees relative to the lateral direction (0° direction) of the photographed area.
[0066] That is, shoot Figure 4 The layer in the photograph shown is the orientation layer.
[0067] In addition, the inorganic fibers of the orientation layer preferably contain 70% or more of inorganic fibers having an inclination angle of 60 to 90 degrees with respect to the width direction of the mat.
[0068] If the orientation layer satisfies the above conditions, the direction in which the tensile stress is applied when the mat is wound coincides with the orientation of the inorganic fibers, and thus the tensile strength of the mat can be easily enhanced, which is preferred.
[0069] Figure 4 The horizontal direction of the photograph shown is the width direction of the mat material, and 78% of the inorganic fibers have an angle θ in the range of 60 to 90 degrees.
[0070] That is, when shooting Figure 4 In the oriented layer of the photograph shown, 70% or more of the inorganic fibers include inorganic fibers having an inclination angle of 60 to 90 degrees with respect to the width direction of the mat.
[0071] The direction with an inclination angle of 60 to 90 degrees with respect to the width direction of the mat can be said to be a direction along the longitudinal direction of the mat. Therefore, it can be said that the inorganic fibers of the orientation layer are oriented along the longitudinal direction of the mat.
[0072] In the orientation layer, the proportion of inorganic fibers having an angle θ of 75 to 90 degrees measured in the lateral direction (0° direction) of the photographing area can be 60% or more, or 70% or more. In addition, the proportion of inorganic fibers having an angle θ of 75 to 90 degrees can be 90% or less, or 80% or less.
[0073] In the orientation layer, the inorganic fibers having an inclination angle of 60 to 90 degrees relative to the width direction of the mat material may contain 75% or more, or 85% or more. In addition, the inorganic fibers having an inclination angle of 60 to 90 degrees relative to the width direction of the mat material may contain less than 95% or less than 90%.
[0074] Figure 5 It is a perspective view schematically showing an example of a random layer.
[0075] Figure 5 The random layer 40 is shown in FIG. 1 , and the inorganic fibers 41 constituting the random layer 40 are schematically shown.
[0076] The random layer 40 is a layer composed of inorganic fibers, and the orientation direction of the inorganic fibers is random.
[0077] In this specification, “random orientation of inorganic fibers” means that in a microscope photograph of inorganic fibers, it can be visually confirmed that the inorganic fibers are not oriented in a specific direction in the photographed region. A layer in which the orientation of inorganic fibers does not fall within the definition of the above-mentioned oriented layer can be referred to as a random layer.
[0078] The oriented layers and random layers in the laminate mat are preferably arranged alternately in the thickness direction. Figure 1 and Figure 2 In the laminate, the random layer 40a / oriented layer 30 / random layer 40b are alternately arranged in this order, and the random layer is arranged on both outermost layers of the laminate mat.
[0079] The number of stacked sheets of the mat in the stacked mat is not particularly limited as long as the oriented layer and the random layer each contain at least one layer. Since the random layer is preferably arranged in the outermost layer and the random layer and the oriented layer are arranged alternately, 3 or 5 sheets are preferably used. Examples include 3 layers of random layer / oriented layer / random layer, and 5 layers of random layer / oriented layer / random layer / oriented layer / random layer.
[0080] The mat constituting the laminated mat comprises inorganic fibers. The inorganic fibers are not particularly limited and may be alumina fibers, silica fibers, etc. In addition, glass fibers or biosoluble fibers may also be used. As long as the characteristics required for the mat material are changed according to heat resistance, wind erosion resistance, etc., it is preferred to use thick-diameter fibers or fibers with long fibers that can adapt to the environmental regulations of various countries.
[0081] Among these, low-crystalline alumina inorganic fibers are preferred, low-crystalline alumina inorganic fibers composed of mullite are more preferred, and inorganic fibers composed of a spinel type compound are further preferred.
[0082] In the mat material of the present invention, the layered mat contains a binder.
[0083] By including a binder in the mat, the frictional force of the mat surface can be increased. Since the binder can easily penetrate into the random layer, it is preferred to penetrate into the random layer.
[0084] The laminate mat preferably contains at least one of an organic binder and an inorganic binder.
[0085] By including a binder in the layered mat, the frictional force of the mat material can be increased.
[0086] Examples of the organic binder include rubber-based resins, styrene-based resins, silicone-based resins, acrylic-based resins, polyester-based resins, and polyurethane resins.
[0087] Examples of the inorganic binder include inorganic sol dispersions (alumina sol, silica sol, zirconia sol, titania sol, etc.).
[0088] The content of the binder contained in the laminated mat (the total amount of the organic binder and the inorganic binder) is preferably 0.2% by weight or more and 30% by weight or less relative to the weight of the laminated mat. In addition, when an organic binder is included, the content of the organic binder is preferably 0.1% by weight or more and 20% by weight or less, and when an inorganic binder is included, the content of the inorganic binder is preferably 0.1% by weight or more and 10% by weight or less.
[0089] When the laminate mat contains a binder, it is preferred that the outermost layer of the laminate mat is a random layer, and an oriented layer is disposed inside the random layer.
[0090] When the adhesive is impregnated into the laminated mat, the adhesive is arranged in the outermost layer of the laminated mat and permeates from the random layer in the thickness direction of the laminated mat. Since the adhesive easily permeates the random layer but not the oriented layer, the adhesive is blocked by the oriented layer in the thickness direction of the laminated mat.
[0091] As a result, the binder content in the outermost layer of the laminated mat, which is in contact with the binder liquid for binder impregnation, increases. If the binder content is high, the frictional force increases, so if the outermost layer with a high binder content is used as the surface in contact with the exhaust gas treatment body requiring friction during winding, the displacement of the exhaust gas treatment body and the mat material can be prevented, and it can be preferably used.
[0092] As a specific example of a structure in which the outermost layer of the laminate mat is a random layer and an oriented layer is arranged inside the random layer, it is preferred that the oriented layer and the random layer are alternately laminated in the thickness direction and random layers are arranged in both outermost layers of the laminate mat.
[0093] In addition, when the laminated pad is divided into three equal parts in the thickness direction, namely, a first surface portion, a central portion, and a second surface portion, a random layer is preferably arranged on the outermost layer of the first surface portion, and the content of the binder in the first surface portion is greater than the content of the binder in the central portion and greater than the content of the binder in the second surface portion.
[0094] Figure 2 In the laminated mat 20 shown in the cross-sectional view of , the random layer 40a, the oriented layer 30, and the random layer 40b are made to have the same thickness, so the random layer 40a can be regarded as the first surface portion, the oriented layer 30 can be regarded as the central portion, and the random layer 40b can be regarded as the second surface portion. In this case, it is preferred that the content of the binder in the random layer 40a is greater than the content of the binder in the oriented layer 30, and greater than the content of the binder in the random layer 40b.
[0095] In the mat material with the random layer arranged as the outermost layer of the first surface portion, since the first surface portion has a high content of the binder, when the first surface portion is used as a portion in contact with the exhaust gas treatment body, the exhaust gas treatment body and the mat material can be prevented from shifting, and can be preferably used.
[0096] In addition, the mat material is used in the exhaust gas purification device, but since the exhaust gas purification device is used in a high temperature environment, the binder (especially the organic binder) may volatilize. Therefore, for the mat material assumed to be used in the exhaust gas purification device, it is required not to increase the binder content.
[0097] In the mat material of the above structure, the content of the binder is increased in the first surface portion instead of increasing the content in the entire mat material, so that the requirements for the binder content of the entire mat material can be met.
[0098] In addition, the content of the binder preferably satisfies the following relationship.
[0099] 0.4≤(central part / first surface part)
[0100] 0.2≤(second surface portion / first surface portion)
[0101] (Second surface / central part)≤0.5
[0102] Furthermore, the content of the binder preferably satisfies the following relationship.
[0103] 0<(second surface part / central part)
[0104] If the adhesive contents of the first surface portion, the central portion, and the second surface portion satisfy the above relationship, when the first surface portion is brought into contact with the exhaust gas treatment body and wound, the friction between the mat and the exhaust gas treatment body is increased, and when assembled into the outer casing, interface sliding is not easily caused between the mat and the exhaust gas treatment body.
[0105] The binder content in the first surface portion is preferably 0.1 wt % to 29.0 wt %, the binder content in the central portion is preferably 0.2 wt % to 15.0 wt %, and the binder content in the second surface portion is preferably 0.05 wt % to 5.0 wt %.
[0106] In the mat of the present invention, the tensile strength at break measured by a tensile test is preferably 200 kPa or more.
[0107] Furthermore, the elongation at break measured by a tensile test is preferably 3.5 mm or less.
[0108] The tensile strength at break and the elongation at break were measured by preparing a sample cut from the mat material to have a length of 200 mm in the longitudinal direction of the mat material and a width of 50 mm in the width direction of the mat material.
[0109] The thickness of the sample was measured at three locations, and a universal material testing machine equipped with a chuck (clamping fixture) for tensile testing was used. The chuck distance was set to 40 mm on one side, and the breaking load and stretching distance were calculated when the pad was stretched along the length direction of the sample at a speed of 100 mm / min.
[0110] Calculate using the following formula:
[0111] Tensile strength at break = load at break / (sample thickness x width).
[0112] The elongation at break was taken as the elongation at break.
[0113] When the tensile strength at break and the elongation at break measured by a tensile test are within the above ranges, it is possible to more reliably prevent the mat from breaking when winding the mat around an exhaust gas treatment body or the like.
[0114] In addition, when the tensile strength at break is high and the elongation at break is small, the variation in workability during winding is reduced.
[0115] The oriented layer and the random layer constituting the laminated mat may be a papermaking mat obtained by a papermaking method or a needle punching mat obtained by a needle punching method.
[0116] In the case of the papermaking method, inorganic fibers such as alumina fibers and silica fibers, inorganic binders and water are mixed in such a way that the content of inorganic fibers in the raw material liquid becomes a specified value, and stirred by a stirrer, thereby preparing a slurry containing inorganic fibers. The slurry can contain a colloidal solution composed of a polymer compound and a resin as needed. Next, the mixed solution is flowed into a former having a filtration screen formed on the bottom surface, and then the water in the mixed solution is dehydrated by the screen, thereby producing a raw material sheet. Afterwards, the raw material sheet is heated and compressed under specified conditions, thereby obtaining a papermaking mat.
[0117] In the case of the needle punching method, for example, a spinning mixture made of alkaline aluminum chloride aqueous solution and silica sol as raw materials is spun by a jet spinning method to produce an inorganic fiber precursor having an average fiber diameter of 3 to 10 μm. Next, the inorganic fiber precursor is compressed to produce a continuous sheet of a predetermined size, which is subjected to a needle punching treatment (needle punching treatment), and then calcined to obtain a needle punched mat.
[0118] The method for producing the oriented layer and the random layer is not particularly limited, and examples thereof include the following methods.
[0119] When the oriented layer is produced by a papermaking method, when a slurry containing inorganic fibers is picked up and made to flow in one direction, the fibers are oriented in the flow direction, and the oriented layer can be formed.
[0120] When the random layer is produced by the papermaking method, a slurry containing inorganic fibers is poured into the mold from above the mold. Since the slurry does not flow, the fibers are not oriented in a specific direction, and a random layer is formed.
[0121] The slurry containing inorganic fibers may contain at least one of an organic binder and an inorganic binder.
[0122] Alternatively, the laminated mat may be a paper-made mat obtained by laminating an oriented layer and a random layer and then subjecting the laminated layer to a needle punching treatment.
[0123] When applying the adhesive to the laminate mat, an adhesive liquid containing the adhesive is allowed to permeate in the thickness direction of the laminate mat from one main surface (referred to as the first main surface) of the laminate mat.
[0124] The binder solution may be impregnated by a method such as curtain coating to allow the binder solution to fall on the mat to impart the binder solution to the inorganic fibers in the mat, or by a method such as spraying to spray the binder solution onto the mat.
[0125] If the random layer is arranged as the outermost layer of the laminate mat and the alignment layer is arranged inside it, the binder easily penetrates the random layer but not the alignment layer. Therefore, the binder is blocked by the alignment layer in the thickness direction of the laminate mat.
[0126] As a result, the binder content in the outermost layer of the laminated mat, which is in contact with the binder liquid for binder impregnation, increases. If the binder content is high, the frictional force increases, so if the outermost layer with a high binder content is used as the surface in contact with the exhaust gas treatment body requiring friction during winding, the displacement of the exhaust gas treatment body and the mat material can be prevented, and it can be preferably used.
[0127] Furthermore, the needle punched mat preferably contains an adhesive and has a rivet portion extending from the first main surface of the layered mat along the needle traces in the thickness direction and having a higher adhesive concentration than other portions.
[0128] Figure 6 is a cross-sectional view schematically showing a needle punched mat including a rivet portion.
[0129] Figure 6 4 shows a rivet portion 51 produced by the adhesive impregnation into a needle trace 50 produced by needling the first main surface 23 of the laminate mat 20 .
[0130] If the needle punched mat has rivets, the binder will penetrate in the thickness direction of the mat, thereby generating constraints between the inorganic fibers, which contributes to the structural reinforcement of the mat, and is therefore preferred.
[0131] The rivet portion is a portion of the laminated mat where the burnt adhesive (organic adhesive) looks like a rivet when the mat material is heated to burn the adhesive (organic adhesive).
[0132] In addition, the depth of the rivet portion is not particularly limited.
[0133] in addition, Figure 6 2 shows that there are needle traces 50 on the second main surface 24 of the laminate mat 20 , but since the adhesive has not penetrated from the second main surface 24 , there is no rivet portion.
[0134] The mat material of the present invention can be used as a holding sealing material for holding an exhaust gas treating body in an exhaust gas purifying device.
[0135] The holding sealing material of the present invention is composed of the mat material of the present invention and is used as a holding sealing material for holding an exhaust gas treating body in an exhaust gas purifying device.
[0136] Figure 7 It is a cross-sectional view schematically showing an example of an exhaust gas purification device.
[0137] like Figure 7As shown, the exhaust gas purification device 100 includes a metal case 130 , an exhaust gas treatment body 120 accommodated in the metal case 130 , and a mat 10 as a holding sealing material disposed between the exhaust gas treatment body 120 and the metal case 130 .
[0138] The exhaust gas treatment body 120 is a columnar component having a plurality of cells 125 arranged in parallel in the length direction with cell walls 126 interposed therebetween. It should be noted that, at the end of the metal shell 130, an inlet pipe for introducing the exhaust gas discharged from the internal combustion engine and an exhaust pipe for discharging the exhaust gas passing through the exhaust gas purification device to the outside are connected as needed.
[0139] The following reference Figure 7 A case where exhaust gas passes through the exhaust gas purification device 100 having the above-mentioned structure will be described.
[0140] like Figure 7 As shown, the exhaust gas ( Figure 7 , G represents exhaust gas, and arrows represent the flow direction of exhaust gas) flows into a channel 125 opened at the exhaust gas inlet side end face 120a of the exhaust gas treatment body (honeycomb filter) 120, and passes through the channel wall 126 separating the channel 125. At this time, PM in the exhaust gas is captured by the channel wall 126, and the exhaust gas is purified. The purified exhaust gas flows out from other channels 125 opened at the exhaust gas outflow side end face 120b and is discharged to the outside.
[0141] Figure 7 In the exhaust gas purification device 100 shown, the holding sealing material is the mat 10 of the present invention. The first main surface 23 of the laminated mat constituting the mat 10 is arranged on one side of the exhaust gas treatment body 120 , and the second main surface 24 is arranged on one side of the metal casing 130 .
[0142] The material of the metal casing constituting the exhaust gas purification device is not particularly limited as long as it is a heat-resistant metal, and specific examples thereof include metals such as stainless steel, aluminum, and iron.
[0143] In addition, the shape of the outer shell may be a clamshell shape, a shape having an approximately elliptical cross section, an approximately polygonal shape, or the like, other than a substantially cylindrical shape.
[0144] Figure 8 It is a perspective view schematically showing an example of an exhaust gas treating body constituting the exhaust gas purification device.
[0145] Figure 8The exhaust gas treatment body 120 shown is a columnar honeycomb structure made of ceramic in which a plurality of cells 125 are arranged in parallel in the length direction via cell walls 126. In addition, any end of the cell 125 is sealed by a sealing material 128. In addition, a peripheral coating 127 is provided on the periphery of the honeycomb structure for the purpose of strengthening the periphery of the honeycomb structure, adjusting the shape, or improving the heat insulation of the honeycomb structure.
[0146] When any end of the cell 125 is sealed, it is preferable that the cells with sealed ends and the cells without sealed ends are arranged alternately when viewed from one end of the exhaust gas treatment body 120 .
[0147] The cross-sectional shape of the exhaust gas treatment body 120 cut in a direction perpendicular to the longitudinal direction is not particularly limited, and may be substantially circular, substantially elliptical, or substantially polygonal such as substantially triangular, substantially quadrilateral, substantially pentagonal, or substantially hexagonal.
[0148] The cross-sectional shape of the pores 125 constituting the exhaust gas treatment body 120 can be roughly polygonal, such as roughly triangular, roughly quadrilateral, roughly pentagonal, roughly hexagonal, or roughly circular or roughly elliptical. In addition, the exhaust gas treatment body 120 can also be composed of pores of various cross-sectional shapes.
[0149] The material constituting the exhaust gas treatment body 120 is not particularly limited, and non-oxides such as silicon carbide and silicon nitride, and oxides such as cordierite and aluminum titanate can be used. Among these, non-oxide porous fired bodies such as silicon carbide and silicon nitride are particularly preferred.
[0150] These porous fired bodies are brittle materials and are easily broken by mechanical shock, etc. However, if a mat material 10 (holding sealing material) is sandwiched around the side of the exhaust gas treatment body 120, the shock can be absorbed, thereby preventing the exhaust gas treatment body 120 from cracking due to mechanical shock or thermal shock.
[0151] The tail gas treatment body may be loaded with a catalyst for purifying tail gas, and as the loaded catalyst, for example, a precious metal such as platinum, palladium, rhodium, etc. is preferred, wherein platinum is more preferred. In addition, as other catalysts, alkali metals such as potassium, sodium, and alkaline earth metals such as barium may also be used. These catalysts may be used alone, or two or more may be used in combination. If loaded with these catalysts, PM is easily burned and removed, and toxic tail gas may also be purified.
[0152] The exhaust gas treatment body constituting the exhaust gas purification device may be an integral honeycomb structure composed of cordierite or the like and formed integrally, or may be an aggregate honeycomb structure formed by bundling a plurality of columnar honeycomb fired bodies (which are composed of silicon carbide or the like and have a plurality of through holes arranged in parallel in the length direction separated by partition walls) by a paste mainly containing ceramics.
[0153] In the exhaust gas treatment body constituting the exhaust gas purification device, the end of the pore may not be sealed without providing a sealing material in the pore. In this case, the exhaust gas treatment body can function as a catalyst carrier for purifying harmful gas components such as CO, HC or NOx contained in the exhaust gas by loading a catalyst such as platinum.
[0154] The holding sealing material of the present invention, which is composed of the mat of the present invention, is wound around an exhaust gas treating body and used. An example in which a wound body formed by winding the holding sealing material around an exhaust gas treating body is arranged in an exhaust gas purifying device will be described.
[0155] Fig. 9 This is a perspective view schematically showing an example of a method for manufacturing an exhaust gas purification device.
[0156] like Fig. 9 As shown, a holding sealing material composed of a mat material 10 is wound around an exhaust gas treating body 120 to form a wound body 140. Next, the wound body 140 is housed in a metal case 130, thereby manufacturing an exhaust gas purifying device.
[0157] When the wound body 140 is produced, the first main surface 23 of the laminated mat 20 constituting the mat material 10 is wound toward the exhaust gas treatment body 120. As a result, the first main surface 23 faces the exhaust gas treatment body 120, and the second main surface 24 faces the metal shell 130.
[0158] Next, as a method for housing the wound body 140 in the metal shell 130, for example, there can be cited: a pressing method (staffing method) of pressing the exhaust gas treatment body 120 (wound body 140) surrounded by a retaining sealing material composed of a cushion material 10 to a predetermined position inside the metal shell 130; a sizing method (swaging form) of compressing from the outer peripheral side to reduce the inner diameter of the metal shell 130; and a clamshell method of setting the metal shell to a shape that can be separated into a first shell and a second shell, placing the wound body 140 on the first shell, and then covering the second shell for sealing; and the like.
[0159] When the wound body is housed in the metal case by a press-fit method (filling method), the inner diameter of the metal case (the inner diameter of the portion housing the exhaust gas treatment body) is preferably slightly smaller than the outer diameter of the wound body.
[0160] Through these steps, the wound body in which the sealing material is wound around the exhaust gas treating body and held can be arranged in the exhaust gas purifying device.
[0161] This specification discloses the following matters.
[0162] The present disclosure (1) is a mat material comprising a layered mat, wherein the layered mat comprises at least one oriented layer composed of inorganic fibers and having a uniform orientation direction, and at least one random layer composed of inorganic fibers and having a random orientation direction, and the layered mat comprises a binder.
[0163] The present disclosure (2) is the mat material as described in the present disclosure (1), wherein the oriented layers and the random layers are alternately stacked in the thickness direction, and the random layers are arranged on both outermost layers of the stacked mat.
[0164] The present disclosure (3) is the mat material according to the present disclosure (1) or (2), wherein the layered mat contains at least one of an organic binder and an inorganic binder.
[0165] The present disclosure (4) is a mat material as described in any one of the present disclosures (1) to (3), wherein when the laminated mat is divided into three equal parts in the thickness direction into a first surface portion, a central portion, and a second surface portion, the random layer is arranged on the outermost layer of the first surface portion,
[0166] The content of the binder in the first surface portion is larger than the content of the binder in the central portion, and larger than the content of the binder in the second surface portion.
[0167] The present disclosure (5) is a mat material as described in the present disclosure (4), wherein the content of the above-mentioned binder satisfies the following relationship.
[0168] 0.4≤(central part / first surface part)
[0169] 0.2≤(second surface portion / first surface portion)
[0170] (Second surface / central part)≤0.5
[0171] The present disclosure (6) is a mat material as described in the present disclosure (5), wherein the content of the above-mentioned binder further satisfies the following relationship.
[0172] 0<(second surface part / central part)
[0173] The present disclosure (7) is a mat as described in any one of the present disclosures (1) to (6), wherein the inorganic fibers in the orientation layer contain 70% or more of inorganic fibers having an inclination angle of 60 to 90 degrees with respect to the width direction of the mat.
[0174] The present disclosure (8) is a mat according to any one of the present disclosures (1) to (7), wherein the tensile strength at break measured by a tensile test is 200 kPa or more.
[0175] Present Disclosure (9) The mat material according to any one of Present Disclosures (1) to (8), wherein the elongation at break measured by a tensile test is 3.5 mm or less.
[0176] The present disclosure (10) is a holding sealing material, which is composed of the mat material described in any one of the present disclosures (1) to (9), and is used for holding an exhaust gas treating body in an exhaust gas purification device.
[0177] Example
[0178] (Example 1)
[0179] A papermaking mat having an oriented layer and a random layer composed of inorganic fibers was prepared by a papermaking method, and the layers were stacked in the order of random layer / oriented layer / random layer / oriented layer / random layer, and needle punched at the same time to prepare a laminated mat.
[0180] A binder liquid containing an organic binder is applied from one main surface (random layer) of the layered mat and dried to produce a mat material.
[0181] The laminated mat is divided into three equal parts in the thickness direction, and the portion containing the random layer on the side provided with the binder liquid is regarded as the first surface portion, and the portion containing the random layer on the opposite side of the side provided with the binder liquid is regarded as the second surface portion. The portion between the first surface portion and the second surface portion is regarded as the central portion.
[0182] The binder content was determined from the weight change before and after the binder liquid was applied.
[0183] Table 1 shows the ratio of the binder content between the first surface portion, the central portion, and the second surface portion, that is, the binder content ratio.
[0184] The photo of the orientation layer is Figure 4 In the photograph shown, 52% of the inorganic fibers have an angle θ of 75 to 90 degrees, and 78% of the inorganic fibers have an inclination angle of 60 to 90 degrees with respect to the width direction of the mat.
[0185] For Figure 4 In the random layer similarly photographed in the shown photograph, 14% of the inorganic fibers have an inorganic fiber angle θ in the range of 75 to 90 degrees, and 27% of the inorganic fibers have an inclination angle of 60 to 90 degrees with respect to the width direction of the mat.
[0186] (Comparative Example 1)
[0187] A mat material (holding sealing material) of Example 1 of Patent Document 1 was prepared.
[0188] The mat of Example 1 of Patent Document 1 is not a laminated mat, and is not a mat having both an oriented layer and a random layer therein.
[0189] (Tensile test)
[0190] The mat was cut into a sample having a length of 200 mm along the longitudinal direction of the mat and a width of 50 mm along the width direction of the mat to prepare.
[0191] The thickness of the sample was measured at three locations, and a universal material testing machine equipped with a chuck (clamping fixture) for tensile testing was used. The chuck distance was set to 40 mm on one side, and the breaking load and stretching distance were calculated when the pad was stretched along the length direction of the sample at a speed of 100 mm / min.
[0192] Calculate using the following formula:
[0193] Tensile strength at break = load at break / (sample thickness x width).
[0194] The elongation at break was taken as the elongation at break.
[0195] The results are shown in Table 1.
[0196] [Table 1]
[0197]
[0198] From the results shown in Table 1, it can be seen that the mat material of Example 1 has high tensile strength.
[0199] Explanation of symbols
[0200] 10. Mat
[0201] 20 layers of mat
[0202] 23. First main surface of the laminated mat
[0203] 24 Second main surface of the laminated mat
[0204] 25 The first long side of the laminated mat
[0205] 26 Second longest side of the laminated mat
[0206] 27 First short side of the laminated mat
[0207] 28 Second short side of the laminated mat
[0208] 30 Orientation layer
[0209] 31 Inorganic fibers constituting the oriented layer
[0210] 40, 40a, 40b random layer
[0211] 41 Inorganic fibers forming random layers
[0212] 50 stitches
[0213] 51 Rivet Department
[0214] 100 Exhaust gas purification device
[0215] 120 Exhaust gas treatment body
[0216] 120a, 120b tail gas inflow side end face
[0217] 125 Channel
[0218] 126 pore wall
[0219] 127 Peripheral coating
[0220] 128 Sealing material
[0221] 130 Metal housing
[0222] 140 winding body
Claims
1. A mat material, wherein: The mat material comprises a laminated mat, wherein the laminated mat comprises at least one oriented layer composed of inorganic fibers and having a uniform orientation direction, and at least one random layer composed of inorganic fibers and having a random orientation direction. The laminate mat includes a binder.
2. The mat material according to claim 1, wherein: The oriented layers and the random layers are alternately stacked in the thickness direction, and the random layers are disposed on both outermost layers of the stacked mat.
3. The mat material according to claim 1 or 2, wherein: The binder is at least one of an organic binder and an inorganic binder.
4. The mat material according to any one of claims 1 to 3, wherein When the laminated mat is divided into three equal parts in the thickness direction, namely, a first surface portion, a central portion, and a second surface portion, the random layer is arranged on the outermost layer of the first surface portion. The content of the binder in the first surface portion is larger than the content of the binder in the central portion, and larger than the content of the binder in the second surface portion.
5. The mat material according to claim 4, wherein: The content of the binder satisfies the following relationship: 0.4≤(central part / first surface part) 0.2≤(second surface portion / first surface portion) (second surface portion / central portion)≤0.
5.
6. The mat material according to claim 5, wherein: The content of the binder further satisfies the following relationship, 0<(second surface portion / central portion).
7. The mat material according to any one of claims 1 to 6, wherein The inorganic fibers of the alignment layer include 70% or more of inorganic fibers having an inclination angle of 60 to 90 degrees with respect to the width direction of the mat.
8. The mat material according to any one of claims 1 to 7, wherein The tensile strength at break measured by a tensile test is 200 kPa or more.
9. The mat material according to any one of claims 1 to 8, wherein The elongation at break measured by a tensile test was 3.5 mm or less.
10. A holding sealing material, comprising the mat material according to any one of claims 1 to 9, and used for holding an exhaust gas treating body in an exhaust gas purification device.
Citation Information
Patent Citations
Holding seal material, manufacturing method of holding seal material, manufacturing method of exhaust gas purification device, and exhaust gas purification device
JP2015063925A
Mat, method for manufacturing the mat, and apparatus for purifying exhaust gas
CN102207018A
Mat, holding sealing material, method for producing mat, and exhaust gas purifying apparatus
CN102444452A
Gasket pad for drum sealing
CN102797850A
Mat material, exhaust gas purification device, and method for manufacturing mat material
CN117412857A